Extraction of chontaduro oil (Bactris gasipaes) for the synthesis of isopropyl esters through transesterification reactions assisted by ultrasound using green solvents - Danny Arteaga; Angie Nathalia Ramírez; Carlos Acevedo; Jaime Martin Franco; Ricardo Benítez Benítez (Applied Biological Chemistry)
Abstract An experimental design study, using the Box-Behnken method with response surface methodologies (RSM), was conducted to evaluate the extraction process of chontaduro pulp (Bactris gasipaes) oil and its potential application in obtaining isopropyl esters through a transesterification process. The extraction of chontaduro oil and the transesterification reactions of the fatty esters were assisted by ultrasound techniques using n-hexane and isopropanol as environmentally friendly solvents. During the extraction process, the parameters evaluated were the sample to solvent ratio (w/w), power amplitude (%), and ultrasound pulse times (s). For the transesterification process, the parameters evaluated were ultrasound amplitude, ultrasound pulse time, and the amount of isopropanol (mol). The optimal conditions for the extraction process were found to be a sample to n-hexane ratio of 1:10 (w/w) and an ultrasound amplitude of 30%, with the pulse time not significantly affecting the oil yield of 15.02% achieved in a total time of 30 min. The predominant fatty acids in chontaduro oil were C18:1 cis oleic acid (54.31%) and C16:0 palmitic acid (20.40%). To synthesize isopropyl esters, we found that the ideal conditions are an ultrasound amplitude of 50%, an ultrasound pulse time of 20 s, and 0.4 moles of isopropanol. These conditions resulted in complete conversion within 45 min. The use of ultrasound radiation proved to be an alternative method to conventional techniques, reducing extraction and transesterification times, minimizing energy consumption, and increasing percentage yield. This contributes to green chemistry and the production of value-added products, potentially useful in the cosmetics industry.